2020
DOI: 10.3390/ijerph17238899
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Related Factors of Nurses Caring for DNR Patients in Intensive Care Units, South Korea

Abstract: This study examined the factors related to burnout, depression, job stress, and job satisfaction in intensive care unit (ICU) nurses caring for do not resuscitate (DNR) patients, as well as analyzed any differences. A cross-sectional descriptive design was employed. Study participants involved a total of 115 nurses caring for DNR patients in ICUs in South Korean hospitals. Measures involved a demographic form, Copenhagen Burnout Inventory (CBI), Center for Epidemiologic Studies Depression Scale, Nursing Job St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
(49 reference statements)
2
11
0
1
Order By: Relevance
“…Our results could be used when planning the organization of educational activities concerning active coping in order to reduce burnout, as the authors from Jordan suggested [ 6 ], which could be a feasible way of addressing the high burnout results. Given that burnout and coping were associated ( Table 2 ), results of this study may be considered in concordance with other studies [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results could be used when planning the organization of educational activities concerning active coping in order to reduce burnout, as the authors from Jordan suggested [ 6 ], which could be a feasible way of addressing the high burnout results. Given that burnout and coping were associated ( Table 2 ), results of this study may be considered in concordance with other studies [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sociodemographic factors such as being younger, single marital status, and having less professional experience in the intensive care unit (ICU were associated with burnout levels [ 24 , 25 , 27 , 29 ]. Age was negatively correlated with EE, and the effort–reward imbalance was positively correlated with EE [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…A high EE score was significantly related to depression and personality factors [ 18 , 29 , 30 ]. Some authors showed that EE was significantly related to four personality factors, neuroticism, agreeableness, responsibility, and extraversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, most of the female HCWs were nurses, and nurses experience higher mental health problems due to their increased exposure and nature of work. Besides, previous studies have shown that nurses and doctors working in the emergency department and intensive care units are at a higher risk of burnout, depression, and job stress compared to their colleagues working in other hospital departments [ 98 , 99 , 100 ]. Therefore, future studies need to rule out these aspects, while determining the effects of a pandemic or epidemic on mental health.…”
Section: Discussionmentioning
confidence: 99%